STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KURIKULUM MERDEKA BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) DI SLB SABILILLAH CUKIR DIWEK JOMBANG - Nizar Farhani; Khairul Umam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education is the right of every individual, including children with special needs (ABK). The independent curriculum provides space for educational units to develop adaptive and student-centered learning, including in determining Islamic religious education learning strategies. Children with Special Needs (ABK) are children who clearly experience obstacles and retardation in intellectual mental development. This study aims to determine the strategy, implementation and what factors are obstacles and supporters in learning Islamic religious education at SLB Sabilillah Cukir Jombang. The method used in this study is qualitative with a case study research type, data obtained through observation, interviews and documentation. The strategy used in Islamic religious education depends on the needs of children such as the mentally retarded using the demonstration strategy and the autistic using the lovees strategy.